2003
DOI: 10.1159/000073449
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Disturbance, Parental Bonding and Alexithymia in Patients with Eating Disorders

Abstract: Background: To evaluate if body image disturbance and alexithymia, two major clinical features of eating disorders (ED), are predicted by an altered parental bonding. Sampling and Methods: 64 female ED outpatients and 68 female healthy controls were assessed by means of the Parental Bonding Instrument (PBI), the Body Uneasiness Test (BUT), and the Toronto Alexithymia Scale (TAS-20). Pearson’s correlations and multiple stepwise regression analysis were applied to explore the contribution of PBI factors on BUT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
47
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 42 publications
13
47
0
1
Order By: Relevance
“…Among males with adjustment disorder, perceived childhood parental overprotection and a low level of care had a perpetuating effect on alexithymia. Previous studies found similar results in that alexithymics recalled a parental rearing style of overprotection or low care [9,10]. In addition, we found patients with higher levels of neuroticism and lower levels of extraversion were more likely to have alexithymic traits; this is consistent with previous studies which found neuroticism had a positive correlation [13] and extraversion a negative correlation with alexithymia [8,14].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Among males with adjustment disorder, perceived childhood parental overprotection and a low level of care had a perpetuating effect on alexithymia. Previous studies found similar results in that alexithymics recalled a parental rearing style of overprotection or low care [9,10]. In addition, we found patients with higher levels of neuroticism and lower levels of extraversion were more likely to have alexithymic traits; this is consistent with previous studies which found neuroticism had a positive correlation [13] and extraversion a negative correlation with alexithymia [8,14].…”
Section: Discussionsupporting
confidence: 91%
“…Twin studies on alexithymia have investigated whether this is a genetically or family environment-induced trait [6][7][8]. Although previous studies have concluded that alexithymia is genetically influenced [6,7], more recent studies support the hypothesis that alexithymia is caused by familial environment factors [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Childhood adversities have also been found to be of particular relevance for depersonalization disorder. In a sample of adult eating disorders, an association of depersonalization with inadequate parental responsiveness was found [45] ; and in a study on a sample of 49 subjects with depersonalization disorder, emotional abuse emerged as the most signifi cant predictor of both depersonalization disorder diagnosis and depersonalization severity compared to healthy controls [46] . The lack of PCs may be regarded as a limitation of the latter study, and thus this fi nding needs further corroboration.…”
Section: Discussionmentioning
confidence: 98%